Evaluation of different strategies to minimize the matrix effects on LC-MS/MS analysis of multiple lipophilic shellfish toxins in both acidic and alkaline chromatographic conditions. (December 2020) - Qiu, Jiangbing; Chen, Huidan; Ji, Ying; Li, Tianshen; Li, Aifeng
Abstract: Lipophilic shellfish toxins (LSTs) accumulated by shellfish pose a potential threat to consumer health. A mandatory routine monitoring of LSTs has been adopted for seafood products by liquid chromatography–mass spectrometry (LC-MS) in many countries. In this study, two methods developed on liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) under acidic and alkaline chromatographic conditions were assessed for the determination of multiple LSTs. Different strategies including matrix solid-phase dispersion (MSPD), solid phase extraction (SPE) and sample dilution were applied and evaluated the matrix effects of mussel, scallop, clam, and oyster samples on the signal response of mass spectrometry. Results showed that the alkaline method achieved a lower limit of detection (LOD) and more robust compared to the acidic method. The obvious signal suppression of OA and DTX1 (55%–76%) and signal enhancement of PTX2 (27%–34%) occurred in the crude extracts of shellfish under acidic chromatography. In the alkaline method, no remarkable matrix effects of crude extracts were found except for the scallop matrix on the signal intensity of DTX1, AZA3 and GYM-A (121%–130%). Clean-up methods MSPD, SPE and sample dilution obviously reduced the inhibition of shellfish matrices on the signal response of OA and DTX1, however, which were still subject to signal inhibition under acidic condition. Sample dilution was more effective than SPE and MSPD in minimizing the matrix interference in both acidic and alkaline methods. Furthermore, sample dilution in combination with the alkaline chromatography was the most effective method. Bivalve mollusks harvested from Beibu Bay, South China Sea, were generally contaminated by GYM-A and SPX1 at low concentrations. Highlights: Matrix effects in the analysis of lipophilic shellfish toxins (LSTs) were assessed. Different strategies were used to remove the interferences of shellfish matrices. Serious matrix effects were observed in crude extracts under acidic condition. No remarkable matrix effects on LSTs response in the alkaline method. Sample dilution combined with the alkaline method was the most efficient approach.